Enhancing Nmax Gen 2 Brake Cooling Through CFD-Based Duct Profile Optimization - Sutrisno, Teng; Chevilino, Marcell; Jonoadji, Ninuk; Siahaan, Ian Hardianto; Sugondo, Amelia; Anggono, Willyanto; Alimin, Roche; Simanjuntak, Melvin E.; Suryajaya, Micheal (Institute of Research and Community Outreach, Petra Christian University, 2026)
Efforts to improve the performance of motorcycle brake system performance are essential for enhancing riding safety, particularly at high speeds. The main objective of this study is to evaluate the effect of a brake duct on brake disc cooling using computational fluid dynamics (CFD). This study also aims to determine the optimal brake duct design for motorcycles applications. To assess the accuracy of the numerical simulations, wind tunnel experiments were conducted to quantify the error between the simulation and experimental results. The validation results showed that the simulation error was 5.64%, indicating good agreement with the experimental data. The simulation was performed by modelling the motorcycle braking system and brake duct, then analyzed using ANSYS Fluent. To identify the optimal brake duct configuration, variations in the inner radius R, duct length L, and diffuser size D were evaluated. The best configuration was defined as the design that produced the lowest pressure loss and the highest ΔP statis. The simulation results indicate that the optimal configuration corresponds to R = 20 mm, L = 180 mm, and D = 8.75mmx 10mm.